Seroprevalence of Zoonotic Protozoa Toxoplasma Gondii Infection in Food Animals of Chattogram Division - Nahar, Sultana Fizun; Saha, Ramesh Prasad; Ashfia, Khan Md; Debnath, Asish Kumer; Rahman, AKM Anisur; Talukder, Md Hasanuzzaman (Research in Agriculture Livestock and Fisheries, 2020)
Toxoplasmosis is a zoonotic protozoan parasitic disease caused by Toxoplasma gondii. The aim of the present study was to determine the prevalence of T. gondii infection in sheep, goats and cattle in Chattogram division. In his study a total of 220 sera samples from different animals were collected from different herds of Chattogram division. Among the 220 samples, 184 sera were examined for T. gondii antibody by indirect Enzyme-Linked Immunosorbent Assay (iELISA) (ID Screen® indirect ELISA kit, IDvet Laboratories, Inc., France) according to the manufacturer’s instructions. Samples with more than 50% S/P were considered as positive for T. gondii. The overall prevalence of T. gondii was 13.59%. The highest prevalence of T. gondii was found in goat 16%, sheep 13.04% and cattle 11.90%. The highest prevalence (36.36%) of T gondii infection was observed in sheep aged >5 years compared to other age groups. Similarly, the highest seroprevalence was found in >18 months old sheep (16.067% compared to <6 months group (5.88%) and pregnant (19.63%) and non-pregnant sheep (11.76%). In contrast to cattle and sheep, the seroprevalence of toxoplasmosis in goats were highest in 6 months to 18 months age group (20.83%) compared to >18 months age group (9.09%). Results indicate that T. gondii infection in food animals in Chattogram division is widespread. Further investigation on the isolation and characterization of T. gondii from the aborted fetus and its zoonotic potential on human population is imperative. The undercooked meat and raw milk of these food animals may serve as a potential source of T. gondi infection for humans. Res. Agric., Livest. Fish.7(2): 275-281, August 2020